Juridical Study on Implementation of Village Chairman Using E-Voting Method - Arif Hijrah Saputra; Widayati Widayati (Universitas Islam Sultan Agung, 2020)
Evidence is a problem that plays a role in the process of trial court examination which aims to find material truth. From the evidence, it is determined whether the defendant is guilty or not. At this stage of evidence, according to Article 52 of the Criminal Procedure Code, the defendant has the right to present mitigating evidence as a defense to give rise to the judge's conviction that he is innocent. The defendant's submission of mitigating evidence is to protect the rights of the defendant and uphold the principle of equality before the law. The evidence presented by the defendant to prove his innocence was documentary evidence. The purpose of this study was to identify and analyze the use of documentary evidence submitted by the defendant in a murder crime case and to find out the weaknesses and solutions to the use of documentary evidence submitted by the defendant in a murder crime case. This legal research uses empirical juridical research methods, by conducting descriptive analysis. This research uses a statutory approach, documents and field research. This legal research is also supported by the results of interviews with informants. Results of the study: The panel of judges accepted the use of documentary evidence by the panel of judges, but the strength of evidence could not be considered in the verdict. The reason is because documentary evidence is not independent evidence and must be supported by other evidence. In accordance with Article 183 of the Criminal Procedure Code, which regulates the minimum number of at least two valid pieces of evidence. The weaknesses of documentary evidence submitted by the defendant include: (a) From a formal perspective, that the power of proof of documentary evidence in a criminal case is controlled by the rules, namely Article 187 KUHAP, they must determine the conviction of the judge. Evidence in a criminal case to seek material truth, the judge is free and not bound by evidence. (b) In terms of material, whereas what is sought in criminal procedural law is material truth, then the consequence is that the judge is free to use or set aside a letter. Although there is no special regulation, according to the negative evidence system (negatief wettelijk bewijstheorie) adopted by the Criminal Procedure Code, namely there must be confidence from the judge regarding the evidence presented at trial. Even though from a formal perspective, the evidence is an official letter, but the value of perfection does not support it to stand on its own and must comply with the principle of the minimum limit of proof stipulated in article 183 KUHAP.